Tawhidic paradigm and ethical leadership: the views of students - Nabi, Ashiqun; Sarif, Suhaimi Mhd (2012)
This paper investigates the influence of Tawhidic paradigm on ethical leadership. The essence of Tawhidic paradigm is in the spiritual built-in conscience and behavior that comply with the law of Allah in discharging duties as servant and vicegerent of Allah religiously. Since Tawhidic paradigm requires a person to discharge duties both for individual and others, it is naturally influences individual to behave ethically and also to be influence others to be equally ethical to seek the Pleasure of Allah. The study obtains the opinions of students through a survey. The preliminary findings suggest that the influence of Tawhidic paradigm is very significant and essential to educate and nurture ethical leadership among students. The informants propose that the academic authority to include Tawhidic paradigm in academic and co-curricular activities as a mean to educate and nurture students to be professional and ethical.